Silent agitators: The role of anxiety in exacerbating hypertension among hospitalized patients in Subang - Sriwinengsih, Wiwin; Nirwana, Bayu (Program Studi Keperawatan, Politeknik Negeri Subang, 2025)
Background: Hypertension is a leading global health concern and a major contributor to cardiovascular diseases and mortality. Anxiety, a common psychological condition, is increasingly recognized for its role in exacerbating hypertension, especially in hospitalized settings. Despite this, the relationship between anxiety and hypertension in such environments remains underexplored. Purpose: This study investigates the relationship between anxiety levels and hypertension exacerbation among patients hospitalized in Subang, Indonesia. Methods: A cross-sectional design was employed, involving 60 hypertensive patients admitted to a regional hospital. Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HAM-A), while blood pressure measurements were recorded during hospitalization. Logistic regression analysis was performed to determine the association between anxiety and blood pressure changes. Results: Results indicated that higher anxiety levels were significantly associated with increased odds of hypertension exacerbation (OR 1.25; p < 0.01). The average HAM-A score was 18.7, reflecting moderate anxiety, and the mean blood pressure change was 12.5 mmHg. Demographic analysis revealed an evenly distributed sample with diverse educational and occupational backgrounds. Conclusion: Anxiety significantly contributes to the destabilization of blood pressure in hospitalized patients, underscoring the need for integrated management strategies that address both psychological and physiological aspects of hypertension. Implementing early identification and targeted interventions for anxiety can improve hypertension outcomes and overall patient care. This study highlights the importance of a holistic approach to hypertension management, particularly in high-stress environments like hospitals.